Hospital Preparedness for COVID-19 in Indonesia: A Case Study in Three Types Hospital - Kristina Dewi; Djazuly Chalidyanto; Agung Dwi Laksono (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The increase in COVID-19 cases demands hospitalpreparedness in handling COVID-19 toprovide quality services by prioritizing patient safety and health personnel factors. The purpose of this studyis to analyze hospital preparedness in providing COVID-19 services comprehensively.Method: The study is a cross-sectional design. The research objects are public, private, and police hospitals.The review usesthe checklist from the CDC.Observation and interviews with hospital leaders carried outdata collection. Data were analyzed descriptively.Result: From the results of filling out theinventory, the preparedness of public, private, and policehospitals in Banjarmasin was low on average. In detail, it showedaverage scores that publichospital(2.83),privatehospital(2.70), and Policehospital(2.63). Police hospital is better prepared than the private and publichospital. Public and private hospitals have the lowest scores on the written COVID-19 Development ofwritten COVID-19 Plan component. Meanwhile, the Police hospital had the lowest scores on consumableand durable medical equipment and supplies.Conclusion: It concludedthe private, public, and police hospitals have a low level of preparednessforCOVID-19 services.